Proliferative and Anti-Inflammatory Effects of Resveratrol and Silymarin on Human Gingival Fibroblasts: A View to the Future - Minoo Shahidi; Farzaneh Vaziri; Ahmad Haerian; Amir Farzanegan; Soudeh Jafari; Roya Sharifi; Fatemeh Sadeghi Shirazi (Tehran University of Medical Sciences, 2017)
Objectives: It has been demonstrated that polyphenol components such as silymarin and resveratrol have anti-inflammatory properties. Periodontitis is a chronic inflammatory disease that leads to the breakdown of dental supporting tissues and tooth loss. The purpose of this study was to investigate the anti-inflammatory effects of silymarin and resveratrol on lipopolysaccharide (LPS)-induced inflammatory response in human gingival fibroblasts (HGFs). Materials and Methods: HGFs were treated with different concentrations of silymarin and/or resveratrol (25, 50, 100 and 200μg/ml). The effects of silymarin and resveratrol on cell viability and proliferation were assessed by MTT assay and cell cycle analysis, respectively. Also, HGFs were treated with silymarin and/or resveratrol and were stimulated with LPS. The levels of Interleukin-6 (IL-6) and IL-8 were assessed by enzyme-linked immunosorbent assay (ELISA).  Results: After treatment with silymarin, the viability of fibroblasts significantly increased, whereas treatment with resveratrol did not have any significant effect on cell viability. However, the combination of these flavonoids (50µg/ml silymarin and 100µg/ml resveratrol) significantly increased the viability of fibroblasts. Resveratrol significantly inhibited LPS-induced IL-6 and IL-8 secretion by HGFs, but silymarin did not show such a significant effect.    Conclusions: The findings of the present study demonstrated the anti-inflammatory effects of resveratrol and its combination with silymarin. Therefore, the combination of silymarin and resveratrol may be useful as a therapeutic agent for treatment of periodontal diseases.